2019
DOI: 10.1097/pcc.0000000000001867
|View full text |Cite
|
Sign up to set email alerts
|

23.4% Hypertonic Saline and Intracranial Pressure in Severe Traumatic Brain Injury Among Children: A 10-Year Retrospective Analysis

Abstract: Objective: To explore the effect of 23.4% hypertonic saline for management of elevated intracranial pressure in children admitted to our institution for severe traumatic brain injury. Design: Single-center, retrospective medical chart analysis. Setting: A PICU at a level 1 pediatric trauma center in the United States. Patients: Children admitted for severe trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Following 10% HS treatment by intravenous injection, the IcP of the rats after MCAO was significantly reduced. This was consistent with the effects of HS on traumatic brain injury (30) and subarachnoid hemorrhage (31).…”
Section: Discussionsupporting
confidence: 87%
“…Following 10% HS treatment by intravenous injection, the IcP of the rats after MCAO was significantly reduced. This was consistent with the effects of HS on traumatic brain injury (30) and subarachnoid hemorrhage (31).…”
Section: Discussionsupporting
confidence: 87%
“…These authors hypothesized that the smaller reduction they observed could be a result of the fact that they only described severe TBI, which could be more refractory to HTS. 8 One possible explanation for any difference in ICP reduction in our study compared with previous studies could be that we enrolled pediatric patients who received 23.4% HTS regardless of indication. The much larger meta-analysis in the adult population, which included all those who were given 23.4% HTS for raised ICP, showed a 50% reduction in ICP comparable to the 37% reduction that we observed.…”
Section: Discussionmentioning
confidence: 78%
“…Because 3% HTS is 0.513 mEq/L and 23.4% HTS is 4 mEq/ L, it delivers equivalent solute at almost an eighth of the volume. 8 This can be useful because fluid overload is frequently cited as an independent risk factor for morbidity and mortality in critically ill pediatric patients. 12,13 A standardized dosing protocol such as ours may be easier for clinicians to remember and, in addition, requires less calculation than weight-based dosing; it also requires less storage space, is easily available because it is aligned with adult practice, and there is reduced variance in delivery of the drug, all helpful in these emergent critical situations.…”
Section: Discussionmentioning
confidence: 99%
“…HS can be used to treat brain edema in clinical settings, which leads to inhibition of NKCC1 expression (Deng et al, 2016;Wu et al, 2019). HS also significantly stimulates NFAT5 expression, which is highly expressed in the fetal brain, and genetically knocking out NFAT5 resulted in an edematous stillborn fetus (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…NFAT5 is a transcription factor that sensitive to extracellular osmolarity and its transcription activation is dramatically increased after HS stimulation (Yang et al, 2018). HS, which inhibits NKCC1 expression (Huang et al, 2014;Rasmussen et al, 2015) is an efficient way to treat brain edema in clinical settings (Bhardwaj and Ulatowski, 2004;Wu et al, 2019). Hence, we assumed that NFAT5 mediate NKCC1 expression in hippocampal neurons after OGD.…”
Section: Nfat5 Is Essential For Moderate Expression Of Nkcc1 In Neuronsmentioning
confidence: 99%